Pattern of Traumatic Dental Injuries and associated Risk Factors: A Hospital-based Study - Shrestha, Deepti; Upadhyay, Sumita (Orthodontic Journal of Nepal, 2018)
Introduction: Study of traumatic dental injuries (TDI);a common dental emergencycan facilitate planning of preventive measures, better assessment and carry out treatment effectively. Objective: To determine the gender and age difference in TDIs, etiology, intra-oral soft-tissue and bony injuries, types of tooth fractures and luxation injuries. Also to find out the association between the type of TDI and malocclusion, overjet and lip competency. Materials & Method: This cross-sectional study comprised of 121 patients with the history of TDI. Thorough history and clinical examination was done and data were statistically analyzed (confidence interval of 95% and statistical significance set at p≤0.05). Result: Males were more prone to injuries with a male-to-female ratio of 1.5:1. Fall and road traffic accidents were the most common cause of injuries and males were more prone to injuries due to fall (p=0.047). The main etiologies of TDIs were fall and RTA in children and adults respectively. Children had more luxation injuries, while adults had more tooth fractures. Permanent maxillary central incisors were most common to sustain tooth fracture and enamel-dentin fracture were the most common types of injuries. No statistically significant association was found between overjet and tooth fractures (p=0.19), luxation injuries (p=0.24), softtissue injuries and bony injuries (p=0.42). Similarly, no significant association was found between lip competency and dental injuries. Conclusion: Cohort studies must be conducted to associate risk factors and TDIs.